Polluter Pays Principle Terkait Pertanggungjawaban Corporate PTTEP Australasia Terhadap Pencemaran Minyak Di Laut Timur Indonesia - Panjaitan, Annisah Dian Utami; Novianti, Novianti; Farisi, Mochammad (Faculty of Law, Universitas Jambi, 2021)
This research is aimed to analyze and determine the 16th provision principle of the declaration on environment and development, namely the polluter pays principle, as one of the state’s form of accountability towards the polluting across borders between PTTEP Australia and Indonesia. This is a juridical research, which analyzes the issue discussed through the use of many realted sources. The Polluter Pyas Principle, as a form of State responsibility in environmental pollution, has some advantages and disadvantages when applied as a recommendation by the OECD (Organization for Economic Cooperation and Development). From a legal perspective, this principle can be applied as a civil liability law, whereas from an economic perspective, it can be viewed as effort to control pollution by means which the polluter has an obligation to pay for the environmental pollution that he/she caused. Even so this principle also has its weakness, in an economic approach this principle is difficult to determine the determination of the cost of loss. In some countries themselves have applied this principle in handling cases of environmental pollution. In the case of cross-border environmental pollution, the principle of good neighborliness and the principle of state responsibility in dealing with pollution cases as a sign of State’s goodwill to comply with existing international law. The case of environmental pollution itself is not only the State that can sue, but a group of people or the community can also sue, if they feel harmed by the pollution that occurs. One of them is by carrying out Class Action in holding accountable for the consequences of pollution that has occurred, and is detrimental to a group or large number of people. Even though international environmental law is a soft law, it can become hard law depending on the pollution case that occurs. Even so, International Environmental Law contained in the Stockholm Declaration, Rio de Jeneiro, Civil Liability Convention and other related international arrangements have been very good in their regulatory fields. Only the state which ratifies the convention applies according to the pollution case that occurs.